Profile of Rectal Cancer Patients Undergoing Radiation Therapy in Dr. Hasan Sadikin General Hospital From 2016 Until 2021 - Kurniadi, Nathanael; Utama, Marhendra Satria; Purnama, Andriana (Indonesian Journal of Cancer, 2024)
Background: Rectal cancer is a type of malignancy that occurs in the rectum. One of the many options of therapy for rectal cancer includes radiotherapy. This research was done to learn about the profile of rectal cancer patients undergoing radiation therapy at Dr. Hasan Sadikin General Hospital from 2016 until 2021. Methods:  A retrospective descriptive study that uses data obtained from patient’s medical records from Dr. Hasan Sadikin General Hospital from 2016 until 2021. The sampling technique used is total sampling from 109 data of rectal cancer patients who underwent radiation therapy in Dr. Hasan Sadikin from 2016 until 2021 Results: : From all 109 rectal cancer patients undergoing radiotherapy, the most often patients found have the age group of 40-49 years old (28.4%), females (50.5%), are mostly found from Priangan area (65.1%), have the chief complaint of a problem with defecating (51.3%), at stage III (36.7%), and have previously received operative management from their previous institutions (42.2%). The patients are mostly undergoing radiotherapy for curative indications (68.8%) and most have a waiting time of more than six weeks before obtaining radiotherapy (61.4%). Conclusions:  Cases of rectal cancer in radiotherapy patients in Dr. Hasan Sadikin General Hospital from the year 2016 to 2021 are seldom compared to other types of cancer and mostly occur in patients aged 40 to 49 years old. Most of the patients come for a curative reason and must wait for more than six weeks before obtaining radiation therapy. Further research may be performed to find the most effective method of giving curative radiotherapy as well as the time given in the hope of making radiotherapy planning more effective in the future.